Standardized preservation, extraction and quantification techniques for detection of fecal SARS-CoV-2 RNA - Natarajan, Aravind; Han, Alvin; Zlitni, Soumaya; Brooks, Erin F.; Vance, Summer E.; Wolfe, Marlene; Singh, Upinder; Jagannathan, Prasanna; Pinsky, Benjamin A.; Boehm, Alexandria; Bhatt, Ami S. (Nature communications, 2021)
Patients with COVID-19 shed SARS-CoV-2 RNA in stool, sometimes well after their respiratory infection has cleared. This may be significant for patient health, epidemiology, and diagnosis. However, methods to preserve stool, and to extract and quantify viral RNA are not standardized. We test the performance of three preservative approaches at yielding detectable SARS-CoV-2 RNA: the OMNIgene-GUT kit, Zymo DNA/RNA shield kit, and the most commonly applied, storage without preservative. We test these in combination with three extraction kits: QIAamp Viral RNA Mini Kit, Zymo Quick-RNA Viral Kit, and MagMAX Viral/Pathogen Kit. We also test the utility of ddPCR and RT-qPCR for the reliable quantification of SARS-CoV-2 RNA from stool. We identify that the Zymo DNA/RNA preservative and the QiaAMP extraction kit yield more detectable RNA than the others, using both ddPCR and RT-qPCR. Taken together, we recommend a comprehensive methodology for preservation, extraction and detection of RNA from SARS-CoV-2 and other coronaviruses in stool. While the analysis of SARS-CoV-2 RNA in stool samples has led to important insights regarding the disease, quantification is currently challenging. Here the authors use patient samples to benchmark preservation, extraction and quantification methods to optimise detection of viral RNA.